Drying Kinetics and Quality of Whole, Halved, and Pulverized Tiger Nut Tubers (Cyperus esculentus) - Ernest Ekow Abano; Joshua Akanson; Nazir Kizzie-Hayford (International Journal of Food Science, 2021)
The objective of this study was to provide the optimum drying conditions to produce high-quality dried tiger nuts using hot-air drying. For this, we evaluated the effect of the whole, halved, and pulverized tiger nuts and air temperature (50 to 70°C) on the drying kinetics and quality of tiger nuts. The drying process generally followed a constant rate in the first 3 hours and a falling regime. We found the optimum drying conditions for tiger nuts to be crushed before convective hot-air drying at a temperature of 70°C. At this optimum condition, the predicted drying time, vitamin C content, reducing sugars, browning, brightness, redness, and yellowness was 780 min, 22.9 mg/100 mg dry weight, 157.01 mg/100 g dry weight, 0.21 Abs unit, 56.97, 1.6, and 17.0, respectively. The tiger nut’s reducing sugars increased from the 130.8 mg/100 dry weight in the raw tiger nuts to between 133.11 and 158.18 mg/100 dry weight after drying. The vitamin C degradation rate was highest in the uncut tiger nuts (32-35%) while in the halved and the pulverized samples, it was between 12 and 17%. The crushed samples’ effective moisture removal increased between 5.6- and 6.75-fold at the different air temperatures than that of the intact tiger nuts. The activation energy was 18.17 kJ/mol for the unbroken, 14.78 kJ/mol for the halved, and 26.61 kJ/mol for the pulverized tiger nut samples. The model MR=0.997 exp−0.02t1.266+0.0000056t was the most suitable thin-layer drying model among the models examined for convective hot-air drying of tiger nuts. It is advisable to crush tiger nut before hot-air drying to produce better-quality flour for making milk beverages, cakes, biscuits, bread, porridge, and tiger nut-based breakfast cereals.